(untitled) (Practitioner Research, 2023)
The reform and practice of the Chinese character literacy teaching method based on the concept of paleography application can be employed to a certain extent and thus will improve the quality of Chinese character literacy teaching. This paper discusses the necessity and feasibility of applying ancient characters to Chinese character literacy teaching, discusses the epistemological and methodological issues of Chinese character literacy teaching, and expounds five teaching methods for the application of ancient characters to Chinese character literacy teaching, including didactic teaching method, case teaching method, theme-based teaching method, situational teaching method, and comprehensive teaching method. Different teaching methods are the deconstruction of Chinese character teaching goals, highlighting teaching objectives and priorities from different levels. They are not isolated and separated from each other, and teachers can actively choose and use teaching methods under the guidance of teaching objectives at different stages.